(untitled) (Research, Society and Development, 2022)
Traumatic brain injury (TBI) is considered one of the most important causes of hospitalization, sequelae and death in Brazil, proving to be a prevalent health problem, in view of the Community welfare. Among the most common causes attributed are traffic accidents. Therefore, this study aimed to determine the current epidemiological profile of patients who were victims of traffic accidents with suspected traumatic brain injury in the city of Cascavel, Paraná, Brazil. The files of 2863 patients from 08/01/2017 to 11/17/2021 were analyzed and it was possible to determine that the profile of these patients is composed of people between 19 and 59 years old involved in traffic accidents involving cars, mainly in the urban area. of the city and, for the most part, have clinical signs and injuries of minimal severity. It is concluded, then, that it is important to implement promising intervention measures, fundamentally focusing on Education and Health.